Effect of lubrication condition on surface roughness in turning operation - Mohd Zulhilmi, Rifin (2010)
Minimum quantity of lubrication (MQL) in machining is an established alternative to completely dry or flood lubricating system from the viewpoint of cost, ecology and human health issues. Hence, it is necessary to select MQL and cutting conditions in order to enhance machinability for a given work material. This thesis describes experimental investigations on influence of different lubrication conditions such as minimum quantity lubrication (MQL), dry machining and wet machining on surface roughness. The surface roughness was examined with Perthometer. In this research, the main objective is to determine the effect of the lubrication conditions on the surface roughness in turning operation. Three different materials had been chosen as work material. Those were ASTM B176 Brass, AISI 1060 Aluminum Alloy and AISI 304 Stainless Steel. Two other parameters were also considered in this study; depth of cut and cutting speed. The ranges of depth of cut used were 0.2mm and 0.4mm whereby the cutting speed values were 810rpm and 1400rpm. Response Surface Method (RSM) was used to predict the surface roughness. Based on the generated results, the correlation for surface roughness with the cutting parameters satisfies a reasonable degree of approximation. It was found that, minimum quantity lubricants produced better surface finish as compared to dry and wet machining. The result can significantly reduce cost and environmental pollution by using minimum quantity lubrication.